PENGARUH TEKNIK REPORTASE DAN QUANTUM WRITING TERHADAP HASIL BELAJAR MENULIS TEKS BERITA - Nukarta, Ali; Mering, Aloysius; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe study was conducted at SMP 3 Kendawangan, Ketapang District, with a sample of 56 students. The learning outcomes of each class are regrouped based on the acquisition of high and low scores so that 2 different groups are formed in each class, speciiically the high learning outcomes group and the low learning outcomes group. The research method used in quantitative research was the experimental method utilizing a 2x2 ANOVA two-way factorial design form. The population in this study were all eighth-grade students of SMP Negeri 3 Kendawangan and the research samples were class VIII A and VIII B. The data collection techniques used were direct observation, interview, measurement, and documentation techniques. The research hypothesis test employs two-way Anava formula and Posthok test. From the results of hypothesis testing, 5 conclusions can be drawn: (1) there are diversity in learning outcomes between reportage techniques and quantum writing techniques; (2) there are differences in learning outcomes between the upper and lower classes; (3) there is no interaction between learning techniques and learning outcomes; (4) there are differences in lower class learning outcomes between reportage and quantum writing techniques.Â Keywords: influence, news, quantum writing, reportage techniques.